Prenatal Detection of Bladder Wall Involvement in Invasive Placentation with Sequential Two-dimensional and Adjunctive Three-dimensional Ultrasonography - Min-Min Chou; Wei-Chi Chen; Jeng-J Tseng; Ya-Fang Chen; Tzu-Ting Yeh; Esther Shih-Chu Ho (Elsevier, 2009)
Objective: The purpose of this study was to determine the diagnostic capability of sequential two-dimensional (2D) and adjunctive three-dimensional (3D) ultrasonography (US) in identifying the location and extent of placental invasion of the bladder. Materials and Methods: Forty-five patients at risk of placenta previa were examined sequentially with 2D US and then with a targeted scan of the region of interest with adjunctive 3D US to determine whether those patients suspected of having advanced invasive placentation by conventional ultrasonographic evidence had placental invasion of the bladder. The images were coded as positive, negative or indeterminate (equivocal) for bladder invasion. Follow-up postoperative outcomes were obtained. Results: Seven of the 45 patients exhibited characteristic ultrasonographic findings for placenta increta/percreta. Among these seven patients with advanced invasive placentation, a targeted scan with adjunctive 3D US correctly provided additional corroborative information to the 2D US indeterminate diagnosis in patients who were found with variable degrees of bladder wall involvement at surgery. Conclusion: 3D US may be a useful adjunctive tool in refining 2D ultrasonographic techniques to identify the extent and degree of placental invasion of the bladder. The advantages of 3D US are: (1) a multiplanar image display allows viewing of sections from sagittal, coronal and axial planes at the same time, thereby more accurately determining the location and extent of placental invasion; (2) the viewing planes of the spatial angioarchitecture network can be arbitrarily manipulated to better delineate the aberrant vessels protruding into the bladder; (3) 3D reconstruction images can be clearly displayed by live 3D in a rotation mode for a better illustrative effect.